Penaeidins, antimicrobial peptides with chitin-binding activity are produced and stored in shrimp granulocytes and released after microbial challenge - Destoumieux, Delphine (2000)
Penaeidins, antimicrobial peptides with chitin-binding activity are produced and stored in shrimp granulocytes and released after microbial challenge